Tribal worlds : critical studies in American Indian Nation building - Hosmer, Brian C., 1960-; Nesper, Larry, 1951- (State University of New York Press, 2013)
This collection explores how Indigenous nationhood has emerged and been maintained in the face of aggressive efforts to assimilate Native peoples.
Keywords: Indians of North America -- Politics and government.; Indians of North America -- Government relatins.; Indians of North America -- Civil rights.; Nationalism -- United States.; Nation-building -- United States.; Self-determination, National -- United States.; United States -- Politics and government.; United States -- Race relations.; Nationalisme -- États-Unis.; Reconstruction d'une nation -- États-Unis.; Droit des peuples à disposer d'eux-mêmes -- États-Unis.; États-Unis -- Politique et gouvernement.; États-Unis -- Relations raciales.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; Indians of North America -- Civil rights; Indians of North America -- Politics and government; Nation-building; Nationalism; Politics and government; Race relations; Self-determination, National; United States